(adsbygoogle = window.adsbygoogle || []).push({}); Question:

solve by using gaussian elimination:

3x - y + z = 1

2x + 2y – 5z = 0

5x + y – 4z = 7

what i did:

step 1: new row 1 = old row 1 – row 2, I got:

x – 3y + 6z = 1

2x + 2y – 5z = 0

5x + y – 4z = 7

step 2: new row 2 = old row 2 – (2 * row1) and new row 3 = old row 3 – (5 * row 1), I got:

x – 3y + 6z = 1

0 + 8y – 17z = -2

0 + 16y – 34z = 2

step 3: new row 3 = old row 3 * (1/2) I got:

x – 3y + 6z = 1

0 + 8y – 17z = -2

0 + 8y – 16z = 1

step 4: new row 3 = old row 3 – row 2, I got:

x – 3y + 6z = 1

0 + 8y – 17z = -2

0 + 0 + z = 3

the Real Answer:

Gaussian elimination gives 0z = 6, ie, 0 = 6 which is clearly impossible.

NO solutions.

i obviously didn’t get that, and i would really appreciate it if someone could check whether i am going wrong somewhere or if my teacher is wrong

thanx

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Gaussian Elimination

**Physics Forums | Science Articles, Homework Help, Discussion**